2019
DOI: 10.1093/annweh/wxz060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Fit of Multiple Consecutive Donning and Doffing of N95 Filtering Facepiece Respirators

Abstract: Background N95 filtering facepiece respirators (FFRs) are widely used in healthcare to reduce transmission of airborne infectious diseases. These respirators are generally described as single use or limited reuse devices, but cost and operational issues mean that they may be donned and doffed multiple times. There is scant research on the effect of this practice on adequacy of fit. Objective The purpose of this study was to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 4 publications
0
46
0
1
Order By: Relevance
“…In addition, fit and filtration are reported to degrade with extended use [98]. Frequent donning and doffing of the same contaminated mask increases HCW contamination risk [99] and compromise fit [100].…”
Section: Rationalementioning
confidence: 99%
“…In addition, fit and filtration are reported to degrade with extended use [98]. Frequent donning and doffing of the same contaminated mask increases HCW contamination risk [99] and compromise fit [100].…”
Section: Rationalementioning
confidence: 99%
“…This is indicative of the fact that FFRs are only able to withstand a certain amount of decontamination cycles before the performance is compromised. Furthermore, studies have suggested that repetitive donning and removal FFRs result in impaired mask fit 29 , indicating that such respirators can only be reused a very small amount of time regardless of the decontamination efficiency. While there are no strict guides explaining the possible number of reuses for FFRs, the CDC recommends no more than 5 reuses based on two studies [29][30][31] .…”
Section: Total Inactivation Of Sars-covmentioning
confidence: 99%
“…Furthermore, studies have suggested that repetitive donning and removal FFRs result in impaired mask fit 29 , indicating that such respirators can only be reused a very small amount of time regardless of the decontamination efficiency. While there are no strict guides explaining the possible number of reuses for FFRs, the CDC recommends no more than 5 reuses based on two studies [29][30][31] . Therefore, a non-deleterious germicidal protocol can be implemented for the decontamination of FFRs to support the safe reuse for a limited number of times.…”
Section: Total Inactivation Of Sars-covmentioning
confidence: 99%
“…It was noted that (including the data for the two replacements FFRs) after 18-19 wearer use sessions on Day 5, the GRPF for all subjects was less than the initial GRPF measured at the time that the FFRs were quantitatively fitted to the subjects (Student's t-test single tail alpha 0.05). However, it remains unclear how much of this degradation is due to reduction in quality of fit, and how much is due to a reduction in the care that was taken to fit the respirator as time progressed (as was concluded by Vuma et al (2019)); this latter factor is difficult to control for in a human study. It is likely that some degradation of quality of fit, as a result of reduced care in donning taken by the wearer, would occur in reality, and that without some form of quantitative check of donning quality on a regular basis, this effect could reduce the protection provided to a wearer over a long period of time by any FFR style, whether new or used.…”
Section: Grpf and Its Correlation With Swpfmentioning
confidence: 99%
“…The reuse of different N95 FFR devices donned and doffed up to 20 times with only 2 min between reuses showed that the protection performance tended to decrease overall but five total wears could be achieved with the FF not dropping below 100 (Bergman et al 2012). In a follow-on study (Vuma et al 2019) evaluating the effect of multiple donnings on respirator fit in health laboratory service employees examining six wears, training of the wearer to maintain repeated correct donning was more important than any loss of ability of the FFR to fit. A report by the Emergency Care Research Institute [ECRI] 2020) on the safety of extended use and reuse of N95 respirators provides practical guidance on the potential risks and benefits that clinical centers should consider during decision making about N95 respirator reuse or extended use.…”
Section: Introductionmentioning
confidence: 96%